2020
DOI: 10.3390/jcm9030671
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Position Facilitates Nasotracheal Intubation with a GlideScope Video Laryngoscope: A Randomized Controlled Trial

Abstract: The optimal head position for GlideScope facilitated nasotracheal intubation has not yet been determined. We compared the neutral and sniffing positions to establish the degree of intubation difficulty. A total of 88 ASA I-II patients requiring nasotracheal intubation for elective dental surgery with normal airways were divided into two groups according to head position, neutral position (group N), and sniffing position (group S). The primary outcome was the degree of intubation difficulty according to the Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In our study, our recommended technique presents a common and simple skill for intubators without head movement and external laryngeal manipulation without needed use of a soft ivory PVC nasotracheal tube. Another study where patients had a pillow positioned below the head while using GlideScope® video laryngoscope‐assisted nasotracheal intubation with nasal Ring–Adair–Elwin tracheal tubes (Mallinckrodt Medical, Covidien, Dublin, Ireland) revealed that 50% of patients required Magill forceps to optimize the maneuver 16 . Our design is presented similar to Kang et al 16 where the head of the patient was placed in a neutral position on a pillow with flexed neck but without changing position such as over‐flexing the neck or turning the neck to the side during tube advancement, and no external laryngeal pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, our recommended technique presents a common and simple skill for intubators without head movement and external laryngeal manipulation without needed use of a soft ivory PVC nasotracheal tube. Another study where patients had a pillow positioned below the head while using GlideScope® video laryngoscope‐assisted nasotracheal intubation with nasal Ring–Adair–Elwin tracheal tubes (Mallinckrodt Medical, Covidien, Dublin, Ireland) revealed that 50% of patients required Magill forceps to optimize the maneuver 16 . Our design is presented similar to Kang et al 16 where the head of the patient was placed in a neutral position on a pillow with flexed neck but without changing position such as over‐flexing the neck or turning the neck to the side during tube advancement, and no external laryngeal pressure.…”
Section: Discussionmentioning
confidence: 99%
“…T A B L E 3 (Continued) Although the study revealed that patients needing auxiliary techniques (Magill forceps or cuff inflation) were 56.7% in the Magill forceps group and 50% in the cuff inflation group, respectively, in other studies, the incidence of using auxiliary techniques is up to 50%. 5,13,15,16 Jones et al reported that using a Portex Polar Preformed Nasotracheal tube with GlideScope ® video laryngoscope and a combination of sophisticated techniques with external laryngeal manipulation and change in head position of the patient enables successful nasotracheal intubation without Magill forceps. 13 In our study, our recommended technique presents a common and simple skill for intubators without head movement and external laryngeal manipulation without needed use of a soft ivory PVC nasotracheal tube.…”
Section: Discussionmentioning
confidence: 99%